In Vitro Analysis of Antibacterial Activity of Black Seed Oil Against Salmonella Typhi - Zulfayanto, Indri; Vanda, Henni; Hambal, Muhammad; Sari, Wahyu Eka; Muttaqien, Muttaqien (Universitas Syiah Kuala, 2025)
Salmonella sp. is one of the bacteria that causes diarrhea in animals and humans, especially in naive animals whose immune systems have not yet been formed. In relation to the emergence of antibiotic resistance against Salmonella typhi, it is necessary to develop an innovation regarding alternative medicines that use herbal medicines as antibacterials, one of which is black seed oil which contains active substances such as thymoquinone. Nigella sativa, commonly known as black seed, has long been used as herbal medicine with many benefits. This study aimed to determine the antibacterial activity of black seed oil against S. typhi bacteria in vitro. This study used S. typhi ATCC 14028, which had been previously re-identified using Gram staining. The black seed oil for the antibacterial test was prepared with three concentrations, 45%, 70%, and 100%, with dimethyl sulfoxide (DMSO) as a negative control and ciprofloxacin as a positive control. Black seed oil's antibacterial test was carried out using the Kirby Bauer method. The data was analysed descriptively. The results showed that black seed oil was not effective in inhibiting the growth of S. typhi, where the inhibition zone formed was less than 5 mm. This is because the antigenic structure of S. typhi has Vi antigens or capsular antigens which are made of polysaccharide polymers found outside the cell to protect the bacteria from outside influences. Therefore, the active ingredients in the black seed oil was unable to reach the site of action on the bacteria so they failed to inhibit or kill the S. typhi bacteria. It can be concluded that the black seed oil used in this study was not effective in inhibiting the growth of S. typhi ATCC 14028